Potent anti-tumor activity of CD45RA-targeting Hm3A4-Ranpirnase against myeloid lineage leukemias. Issue 4 (1st April 2022) - Li, Sisi; Wang, Zhujun; Guo, Xiaoping; Chen, Ping; Tang, Yongmin
ABSTRACT: CD45RA is a specific marker for leukemia stem cell (LSC) sub-populations in acute myeloid leukemia (AML). Ranpirnase (Rap), an amphibian RNase, has been extensively investigated in preclinical and clinical studies for its antitumor activity. Rap could be administered repeatedly to patients without inducing an immune response. Reversible renal toxicity has been reported to be dose-limiting. In this study, we generated a novel immunotoxin targeting LSCs: Hm3A4-Rap, which was composed of Rap and Hm3A4, a human-mouse chimeric antibody against CD45RA. This immunotoxin was generated recombinantly by fusing Rap to Hm3A4 at the Fc terminus and then produced by stably transfecting CHO cells. The immunotoxin was purified using Ni-NTA and then evaluated using RT-PCR, SDS-PAGE, antibody titer assays, competitive inhibition assays, and internalization assays. In addition, the purity, molecular integrity, and affinity to the CD45RA antigen were determined. In vitro studies demonstrated that Hm3A4-Rap could efficiently kill target cells. In vivo studies demonstrated that Hm3A4-Rap had potent anti-leukemia activity, with dosed mice showing a significant increase in survival time compared to control mice (P < 0.01). In summary, our immunotoxin had excellent biological activity suggesting its potential therapeutic value for treating AML patients. Additional preclinical and clinical studies are needed to develop this immunotoxin as a treatment option for patients with leukemia. Graphical Abstract: uf0001